Intravascular ultrasound for peri-procedural geometric orifice area measurement during transcatheter pulmonary valve replacement. (14th October 2021) - Kalinczuk, L; Wozniak, O; Mintz, G S; Rynkiewicz, K; Skotarczka, W; Zielinski, K; Michalowska, I; Biernacka, K; Ruzyllo, W; Demkow, M
Abstract: Introduction: Large imaging filed intravascular ultrasound (IVUS) offering superior online tomographic perspective and visual accuracy could guide transcatheter pulmonary valve replacement (TPVR) for right ventricular outflow tract (RVOT) insufficiency. It is unknown whether geometric orifice area (GOA) measured by IVUS corresponds with effective orifice area (EOA) measure by transthoracic echocardiography (TTE) after successful TPVR. Purpose: To compare minimal inner-leaflets cross-sectional area delineated in systole (min GOA) measured by IVUS versus EOA calculated = right ventricle stroke volume (measured in baseline cardiac magnetic resonance) / pulmonary valve velocity time integral (measured early post-procedure by Vivid e95). Methods: After successful TPVR a 10MHz Vision PV 0.035" (60mm imaging field) IVUS catheter was slowly pulled from the distal pulmonary artery to the right ventricle with continuous imaging of RVOT. IVUS measurements included inner-valve dimension for several evenly spaced cross-sections along the entire length and perpendicular to RVOT long axis. Measured were outer-frame diameters (minimal and maximal) and its cross-sectional area, and cross-sectional area of the visual orifice (min GOA) identified exclusively at the coaptation site (Fig 1). Results: There were 11 pts (median age 30 [25–36] yrs, 4 ♀, all but one with Tetralogy of Fallot) who had undergone prior corrective surgery (5 transannular patch, 2 bioprosthetic valve or 4 pulmonary homograft). Overall, 176 cross-sections were analyzed. Overall, min GOA measured 3.7±1.0cm 2, and was 68%±9% of the valve-outer area (5.5±1.5cm 2 ). It was substantially larger than calculated EOA (3.7±1.0cm 2 vs 2.0±0.5cm 2 ; p<0.001). The ratio of max/min GOA diameter was 1.11±0.11 signifying low eccentricity and was not related to EAO. Conclusions: After successful balloon-expandable valve implantation to treat RVOT insufficiency, geometric orifice dimension was significantly smaller then outer valve frame dimension. Visual measure of geometric orifice area during the procedure using IVUS documented its circularity and indicated that it was larger than EOA calculated upon functional measure. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): This work was supported by the research grant (2.4/VI/18) founded by the National Institute of Cardiology in Warsaw (Poland).